2021
DOI: 10.12932/ap-151118-0439
|View full text |Cite
|
Sign up to set email alerts
|

Food allergy in nursery children of Kawasaki city, Japan

Abstract: Background: Food allergies are often life threatening. In order to establish appropriate food allergy measures in nursery children, it is important to analyze local epidemiological data on the food allergy prevalence in nursery children. However, no such data are currently available for the city of Kawasaki, Japan.Objective: The present study retrospectively evaluated food allergy prevalence among nursery children in Kawasaki city.Methods: Data from children with food allergies requiring food avoidance in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Thus, as food allergy emergency in children potentially can lead serious problems at nurseries [ 5 ], Kawasaki city office has been setting several kinds of preventive measures for food allergy emergency, including the registration of children with food allergy, elimination diets, the instruction of epinephrine auto-injection kit and the preparation of emergency manuals. According to the registration of food allergy, high percentage of nurseries in Kawasaki city has cared for food allergy children [ 2 ]. According to the increase of allergy children, introducing certifications about allergy by medical doctors are essential in nurseries in order to pick up allergic children at risk [ 2 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, as food allergy emergency in children potentially can lead serious problems at nurseries [ 5 ], Kawasaki city office has been setting several kinds of preventive measures for food allergy emergency, including the registration of children with food allergy, elimination diets, the instruction of epinephrine auto-injection kit and the preparation of emergency manuals. According to the registration of food allergy, high percentage of nurseries in Kawasaki city has cared for food allergy children [ 2 ]. According to the increase of allergy children, introducing certifications about allergy by medical doctors are essential in nurseries in order to pick up allergic children at risk [ 2 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the registration of food allergy, high percentage of nurseries in Kawasaki city has cared for food allergy children [ 2 ]. According to the increase of allergy children, introducing certifications about allergy by medical doctors are essential in nurseries in order to pick up allergic children at risk [ 2 6 ]. In this study, only 4 cases of anaphylaxis have been reported for a 1 year, while many children with food allergy have been in nurseries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, the number of children with food allergies is increasing, and 8% of children in the USA and 5% of young children in Japan have food allergies [1,2]. In a single Japanese urban center, the incidence of food allergies has been demonstrated to escalate annually [3]. Childhood food allergy decreases family quality of life and confers nutritional and financial burdens [4].…”
Section: Introductionmentioning
confidence: 99%
“…Food allergy (FA) is a major public health issue globally, affecting about 8% of children and 10% of adults (see Fig 1 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 for global prevalence data). FA has a negative impact on the lives of patients with allergy and their families, and there is no curative treatment.…”
mentioning
confidence: 99%